Copper thiovanadate for magnesium-sodium hybrid battery and preparation method of copper thiovanadate

Copper thiovanadate was prepared by hydrothermal method and its morphology was controlled by adjusting the pH value, which solved the problems of unenvironmental and poor electrical performance of the existing preparation methods, and achieved an efficient and environmentally friendly preparation process and excellent electrical performance.

CN119750644APending Publication Date: 2025-04-04CHONGQING UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411943140.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing preparation methods of copper thiovanadate are not environmentally friendly and have poor electrical performance, making it difficult to meet the needs of magnesium-sodium mixed batteries.

Method used

Copper thiovanadate was prepared by hydrothermal method, and by adjusting the pH value of the reaction system, its micromorphology was controlled to be regular spherical, and its electrical properties were improved.

Benefits of technology

It has achieved efficient preparation of copper thiovanadate, with a yield of up to 98%. It has excellent specific capacity and good circulation effect. The first circle capacity can reach 427.15mAh/g, and is suitable for the positive electrode of magnesium-sodium mixed battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119750644A_ABST
    Figure CN119750644A_ABST
Patent Text Reader

Abstract

The invention discloses copper thiovanadate for a magnesium-sodium hybrid battery, the microstructure of the copper thiovanadate is in a regular sphere-like shape, and the particle size of the copper thiovanadate is 3-5 [mu] m. The invention also provides a preparation method of the copper thiovanadate. According to the preparation method provided by the invention, copper thiovanadate is prepared by utilizing a simple hydrothermal method, and the final synthesis yield can reach 98%; meanwhile, by regulating and controlling the pH value of a reaction system, the prepared copper thiovanadate is precisely regulated and controlled to be in a regular sphere-like shape and is used for a magnesium-sodium ion battery positive electrode. The specific capacity shown by the regular spherical morphology is excellent, the circulation effect is good, and the first-circle capacity can reach 427.15 mAh / g. Meanwhile, the preparation method is simple and convenient in process, wide in applicability, high in safety performance, accurate in morphology regulation and control, low in reaction raw material and equipment requirements and capable of being popularized and applied on a large scale.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of chemistry and energy storage technology, and specifically relates to copper thiovanadate for magnesium-sodium hybrid battery and a preparation method thereof. Background Art

[0002] With the development of society, fossil fuels (coal, oil, natural gas, etc.) are consumed in large quantities. The two major problems facing the world today are energy crisis and environmental degradation. One of the ways for countries around the world to solve these problems is to develop green, renewable and clean energy. In recent years, under the dual carbon goals, my country's energy transformation has gradually turned to green progress, and the proportion of non-fossil energy consumption has continued to increase. With the rapid growth of renewable energy, the power system lacks greater flexibility and cannot ensure that variable renewable energy can be fully and effectively concentrated in the power system, accompanied by a large-scale increase in electric vehicles. The development of energy storage devices is seen as one of the solutions to promote the effective integration of renewable energy. Lithium-ion batteries (LIBs) are one of the most widely used and successful energy storage devices at present because of their high voltage, good specific capacity and suitable operating temperature; however, their energy density can only reach up to 300Wh / kg; in addition, the scarcity of lithium resources and the safety of lithium dendrites have seriously restricted the further development and application of lithium-ion batteries; based on the current situation, the further development of new electrochemical energy storage devices other than lithium batteries is also a top priority.

[0003] As one of the representatives of multivalent ion batteries, magnesium ion batteries (MIBs) have also emerged in recent years and have been widely studied. In the periodic table, magnesium and lithium are located on the diagonal position, and the two have similar chemical properties. Compared with lithium, magnesium has the advantages of abundant resources (2.3% of the earth's crust reserves are 1045 times that of lithium reserves (0.0022%)), simple synthesis process, and low cost. At the same time, the divalent nature of magnesium ions allows it to carry and store more charge, and magnesium ion batteries have a higher volumetric capacity (3833mAh / cm -3 ). Most importantly, the magnesium negative electrode is relatively stable in the air and will not produce dendrites, which greatly improves safety performance; based on the above advantages of magnesium-ion batteries, the development of high-performance magnesium-ion batteries has great prospects.

[0004] Although magnesium-ion batteries have certain development potential, their positive electrode, negative electrode and electrolyte still have a series of problems. For example, magnesium ions have a small ionic radius and high charge density, and positive electrode materials are easily combined with solvents, which will cause serious solvation. Only a few positive electrode materials can effectively achieve reversible insertion / extraction of magnesium ions. Sulfides are considered to be the most promising positive electrode materials for magnesium-ion batteries due to their special properties.

[0005] Among them, sulfide Cu 3 VS 4The commonly used synthesis method is solid-phase synthesis, which is specifically solid-phase calcination at above 900°C under closed conditions in a quartz tube. This method requires expensive raw materials and equipment, and the operation process is relatively complicated. In 2022, Chen et al. (Chemical Engineering Journal 446 (2022) 136772) reported the use of a solvothermal method. The raw materials for this method are vanadium acetylacetonate (1.393g 4mmol), copper nitrate trihydrate (0.161g 0.66mmol), thioacetamide (0.301g4mmol) and methanol (35ml). Although this method is simple in synthesis, it involves organic solvent heat, which is dangerous and not convenient for large-scale synthesis. Summary of the invention

[0006] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the main purpose of the present invention is to provide a copper thiovanadate for magnesium-sodium hybrid battery, aiming to solve the problem that the existing preparation method of copper thiovanadate is not environmentally friendly and has poor electrical performance.

[0007] The main purpose of the present invention is to provide a method for preparing copper thiovanadate for magnesium-sodium hybrid batteries.

[0008] The objective of the present invention is achieved through the following technical solutions:

[0009] A copper thiovanadate for a magnesium-sodium hybrid battery, wherein the microscopic morphology of the copper thiovanadate is a regular spherical shape and the particle size is 3-5 μm.

[0010] A method for preparing the aforementioned copper thiovanadate for magnesium-sodium hybrid battery comprises the following steps:

[0011] 1) Grind the copper source, the vanadium source and the sulfur source in a mortar respectively and add them into deionized water. After stirring evenly at room temperature, adjust the pH value of the system to 2-3 to obtain a mixed solution;

[0012] 2) The mixed solution obtained in step 1) is transferred to deionized water, mixed evenly, and then heated for reaction; after the reaction is completed, the mixture is cooled, centrifuged, and dried to obtain regular spherical copper thiovanadate.

[0013] In some specific embodiments, the copper source is any one or a combination of at least two of copper fluoride, copper chloride, copper bromide, copper nitrate, copper sulfate, copper carbonate, copper oxalate, copper acetate, basic copper carbonate, copper hydroxide, copper oxide, copper sulfide and copper acetylacetonate.

[0014] In some specific embodiments, the vanadium source is any one of ammonium metavanadate, vanadium acetylacetonate, sodium orthovanadate, or a combination of at least two thereof.

[0015] In some specific embodiments, the sulfur source is any one of thioacetamide, thiourea and L-cysteine, or a combination of at least two thereof.

[0016] In certain specific embodiments, the molar ratio of the copper source, the vanadium source and the sulfur source is 3:1:6-20.

[0017] In certain specific embodiments, the molar concentration of the vanadium source in step 1) is 0.013-0.02 mol / ml, the molar concentration of the copper source is 0.04-0.06 mol / ml, and the molar concentration of the sulfur source is 0.026-0.4 mol / ml.

[0018] In some specific embodiments, the volume of the mixed solution in step 2) accounts for 1 / 2-3 / 4 of the total volume of the reaction system.

[0019] In certain specific embodiments, the process conditions for the heating reaction in step 2) are: reacting at a temperature of 160-230° C. for 2-3 days.

[0020] In certain specific embodiments, the process conditions for centrifugation in step 2) are: taking the cooled reaction solution and placing it in a centrifuge tube, centrifuging it alternately with deionized water and ethanol for 2-5 times, the centrifugation rate is 8000-12000rpm, each centrifugation time is 2-10min, and the supernatant is removed; the process conditions for drying are: drying in a vacuum oven at 50-70°C for 10-15h.

[0021] Compared with the prior art, the present invention has at least the following advantages:

[0022] 1) The preparation method provided by the present invention uses a simple hydrothermal method to prepare copper thiovanadate, and the final yield of the synthesis can be as high as 98%; at the same time, by adjusting the pH of the reaction system, the morphology of the prepared copper thiovanadate is precisely adjusted to be a regular spherical shape, which is used for the positive electrode of magnesium-sodium ion battery. The copper thiovanadate with a regular spherical morphology exhibits excellent specific capacity and good cycle effect, and the first cycle capacity can reach 427.15mAh / g.

[0023] 2) The preparation method of the present invention has simple process, wide applicability, high safety performance, precise control of its morphology, low requirements for reaction raw materials and equipment, and can be promoted and applied on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the specific embodiments of the present invention, the drawings required for use in the specific embodiments or the description of the prior art will be briefly introduced below.

[0025] Figure 1 XRD result diagram of the copper thiovanadate positive electrode material with a control system pH of 6.9 provided in Comparative Example 1 of the present invention;

[0026] Figure 2 The XRD result diagram of the copper thiovanadate positive electrode material with a control system pH of 2.9 provided in Example 1 of the present invention;

[0027] Figure 3 The XRD result diagram of the copper thiovanadate positive electrode material with a control system pH of 1.9 provided in Comparative Example 2 of the present invention;

[0028] Figure 4 This is a SEM result of the copper thiovanadate positive electrode material with a pH of 2.9 in the control system provided in Example 1 of the present invention;

[0029] Figure 5 This is a SEM result of the copper thiovanadate positive electrode material with a pH of 6.9 in the control system provided in Comparative Example 1 of the present invention;

[0030] Figure 6 This is a SEM result of the copper thiovanadate positive electrode material with a pH of 1.9 in the control system provided in Comparative Example 2 of the present invention;

[0031] Figure 7 A comparison diagram of the first-cycle electrochemical performance curves of the copper thiovanadate positive electrode material at a current density of 50 mA / g with the control system pH of 6.9, 2.9, and 1.9 provided in Example 1 of the present invention;

[0032] Figure 8 This is a long cycle performance curve of the copper thiovanadate positive electrode material with a control system pH of 2.9 at 1 A / g provided in Example 1 of the present invention. DETAILED DESCRIPTION

[0033] The present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments. The following embodiments are only illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.

[0034] When a certain amount, concentration or other value or parameter is expressed in the form of a range, a preferred range, or a preferred upper and lower numerical limit, it should be understood that it is equivalent to specifically revealing any range by combining any pair of upper range limits or preferred numerical values ​​with any lower range limit or preferred numerical value, regardless of whether the range is specifically disclosed. Unless otherwise indicated, the numerical range values ​​listed herein include the endpoints of the range, and all integers and fractions within the range.

[0035] Unless otherwise indicated, all percentages, parts, ratios, etc. herein are by weight.

[0036] The materials, methods, and examples herein are illustrative and are not to be construed as limiting unless specifically stated.

[0037] In the following embodiments, the copper source is any one or a combination of at least two of copper fluoride, copper chloride, copper bromide, copper nitrate, copper sulfate, copper carbonate, copper oxalate, copper acetate, basic copper carbonate, copper hydroxide, copper oxide, copper sulfide and copper acetylacetonate;

[0038] The vanadium source is any one of ammonium metavanadate, vanadium acetylacetonate, and sodium orthovanadate, or a combination of at least two of them.

[0039] The sulfur source is any one of thioacetamide, thiourea and L-cysteine ​​or a combination of at least two of them.

[0040] Example 1

[0041] The preparation method of copper thiovanadate for magnesium-sodium hybrid battery provided in this embodiment comprises the following steps:

[0042] 1) grinding a copper source, a vanadium source and a sulfur source (wherein the vanadium source is ammonium metavanadate, the copper source is copper chloride dihydrate, and the sulfur source is thiourea) in a molar ratio of 3:1:20 respectively in a mortar and adding them into 60 ml of deionized water, stirring evenly at room temperature, and adjusting the pH value of the system to 2.9 with citric acid to obtain a mixed solution;

[0043] That is, the molar concentration of the vanadium source is 0.017 mol / ml, the molar concentration of the copper source is 0.05 mol / ml, and the molar concentration of the sulfur source is 0.33 mol / ml;

[0044] 2) The mixed solution obtained in step 1) was transferred to 60 ml so that the volume of the mixed solution accounted for 1 / 2 of the total volume of the reaction system. After mixing evenly, the mixture was heated to 200° C. for reaction for 2 days, and then cooled to room temperature to obtain a reaction solution;

[0045] 3) The cooled reaction solution was placed in a centrifuge tube, and centrifuged alternately with deionized water and ethanol for 3 times at a centrifugal speed of 10,000 rpm, each centrifugation time of 8 minutes, and the supernatant was removed; the drying process conditions were: drying in a vacuum oven at 60° C. for 12 hours to obtain copper thiovanadate for magnesium-sodium hybrid batteries.

[0046] Example 2

[0047] The preparation method of copper thiovanadate for magnesium-sodium hybrid battery provided in this embodiment comprises the following steps:

[0048] 1) grinding a copper source, a vanadium source and a sulfur source (wherein the vanadium source is ammonium metavanadate, the copper source is copper chloride dihydrate, and the sulfur source is thiourea) in a molar ratio of 3:1:20 respectively in a mortar and adding them into 60 ml of deionized water, grinding them uniformly at room temperature, and adjusting the pH value of the system to 2.57 with citric acid to obtain a mixed solution;

[0049] That is, the molar concentration of the vanadium source is 0.017 mol / ml, the molar concentration of the copper source is 0.05 mol / ml, and the molar concentration of the sulfur source is 0.33 mol / ml;

[0050] 2) The mixed solution obtained in step 1) was transferred to 60 ml so that the volume of the mixed solution accounted for 1 / 2 of the total volume of the reaction system. After mixing evenly, the mixture was heated to 180° C. for reaction for 3 days and cooled to room temperature to obtain a reaction solution;

[0051] 3) The cooled reaction solution was placed in a centrifuge tube, and centrifuged alternately with deionized water and ethanol for 3 times at a centrifugal speed of 10,000 rpm, each centrifugation time of 8 minutes, and the supernatant was removed; the drying process conditions were: drying in a vacuum oven at 60° C. for 12 hours to obtain copper thiovanadate for magnesium-sodium hybrid batteries.

[0052] Comparative Example 1

[0053] The preparation method of copper thiovanadate for magnesium-sodium hybrid batteries provided in this comparative example is basically the same as that in Example 1, except that no pH adjustment is performed in step 1), that is, no citric acid adjustment system is used, and the pH value in the system is maintained at 6.9.

[0054] Comparative Example 2

[0055] The preparation method of copper thiovanadate for magnesium-sodium hybrid battery provided in this comparative example is basically the same as that in Example 1, except that citric acid is used in step 1) to adjust the pH value of the system to 1.9.

[0056] Performance test example:

[0057] This application takes Example 1 as an example, performs performance tests on the copper thiovanadate prepared in Example 1 and Comparative Example 2, and conducts phase exploration on Comparative Example 1 without pH control, specifically:

[0058] 1) Exploration of phases at different pH

[0059] In this test example, the crystal structure of the copper thiovanadate prepared in Example 1 and Comparative Examples 1-2 was tested by using an XRD diffractometer. The XRD patterns of the copper thiovanadate obtained by the reaction at pH values ​​of 6.9, 2.9, and 1.9 were Figure 1 , 2 As shown in Figure 3, it can be seen from the figure that when the pH is not adjusted, the pH of the synthesis system is 6.98, and copper thiovanadate at this pH has a mixed phase, while the XRD after the pH is adjusted (pH is 2.88 and 1.9) shows a pure phase.

[0060] 2) Microscopic morphology

[0061] In this test example, the microscopic morphology of the copper thiovanadate prepared in Example 1 and Comparative Examples 1-2 was tested by using a scanning electron microscope, wherein the SEM images of the copper thiovanadate obtained by the reaction at pH 2.9, 6.9, and 1.9 were respectively Figure 4 , 5 As shown in Figure 6, it can be seen from the figure that the morphology of the copper thiovanadate prepared in Example 1 of the present application is regular spherical, while the morphology of the copper thiovanadate prepared in Comparative Example 1 is irregular spherical, and the morphology of the copper thiovanadate prepared in Comparative Example 2 is stacked in sheets.

[0062] 3) Electrical properties

[0063] Test method: A full battery with Mg as the negative electrode, copper thiovanadate as the positive electrode, and MACT+NaT as the electrolyte was assembled and charged, discharged, and cycled at a current density of 50 mA / g using a Xinwei charging and discharging device.

[0064] Results and Discussion:

[0065] The electrochemical performance of copper thiovanadate obtained by the reaction at pH 2.9, 6.9, and 1.9 at a current density of 50 mA / g is shown in the figure below: Figure 7 As shown in the figure, it can be seen that the electrical performance of the copper thiovanadate prepared in Example 1 of the present application at 50mA / g in the first cycle is 427.15mAh / g; the electrical performance of the copper thiovanadate prepared in Comparative Example 1 at 50mA / g in the first cycle is 166.33mAh / g; the electrical performance of the copper thiovanadate prepared in Comparative Example 2 at 50mA / g in the first cycle is 228.05mAh / g, indicating that the copper thiovanadate prepared in the present application has excellent electrical properties.

[0066] 4) Cycle performance test

[0067] Test method: A full battery with Mg as the negative electrode, copper thiovanadate as the positive electrode, and MACT+NaT as the electrolyte was assembled and subjected to a cyclic test on the Xinwei charging and discharging equipment at a current density of 1A / g.

[0068] Test results such as Figure 8 As shown, Figure 8 This is a long cycle performance curve of the copper thiovanadate positive electrode material with a pH value of 2.9 in the control system in Example 1 of the present application at 1A / g. It can be seen from the figure that the capacity of the copper thiovanadate positive electrode material reaches 177mAh / g after cycling at 1A / g, and the capacity retention rate is 77% and the coulombic efficiency remains 100% after 500 cycles, indicating that it has excellent cycle stability.

[0069] In summary, the spherical copper thiovanadate prepared in the present application has excellent electrical properties.

[0070] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.

Claims

1. A copper thiovanadate for magnesium-sodium hybrid battery, characterized in that: The microscopic morphology of the copper thiovanadate is regular spherical, and the particle size is 3-5 μm.

2. A method for preparing copper thiovanadate for magnesium-sodium hybrid battery according to claim 1, characterized in that: The steps include: 1) Grinding the copper source, vanadium source and sulfur source in a mortar respectively and adding them into deionized water, stirring them evenly at room temperature, and adjusting the pH value of the system to 2-3 to obtain a mixed solution; 2) The mixed solution obtained in step 1) is transferred to deionized water, mixed evenly, and then heated for reaction; after the reaction is completed, the mixture is cooled, centrifuged, and dried to obtain regular spherical copper thiovanadate.

3. The method for preparing copper thiovanadate for magnesium-sodium hybrid battery according to claim 1, characterized in that: The copper source is any one or a combination of at least two of copper fluoride, copper chloride, copper bromide, copper nitrate, copper sulfate, copper carbonate, copper oxalate, copper acetate, basic copper carbonate, copper hydroxide, copper oxide, copper sulfide and copper acetylacetonate.

4. The method for preparing copper thiovanadate for magnesium-sodium hybrid battery according to claim 1, characterized in that: The vanadium source is any one of ammonium metavanadate, vanadium acetylacetonate, and sodium orthovanadate, or a combination of at least two of them.

5. The method for preparing copper thiovanadate for magnesium-sodium hybrid battery according to claim 1, characterized in that: The sulfur source is any one of thioacetamide, thiourea and L-cysteine ​​or a combination of at least two of them.

6. The method for preparing copper thiovanadate for magnesium-sodium hybrid battery according to claim 1, characterized in that: The molar ratio of the copper source, the vanadium source and the sulfur source is 3:1:6-20.

7. The method for preparing copper thiovanadate for magnesium-sodium hybrid battery according to claim 1, characterized in that: In step 1), the molar concentration of the vanadium source is 0.013-0.02 mol / ml, the molar concentration of the copper source is 0.04-0.06 mol / ml, and the molar concentration of the sulfur source is 0.026-0.4 mol / ml.

8. The method for preparing copper thiovanadate for magnesium-sodium hybrid battery according to claim 1, characterized in that: The volume of the mixed solution in step 2) accounts for 1 / 2-3 / 4 of the total volume of the reaction system.

9. The method for preparing copper thiovanadate for magnesium-sodium hybrid battery according to claim 1, characterized in that: The process conditions for the heating reaction in step 2) are: reacting at a temperature of 160-230° C. for 2-3 days.

10. The method for preparing copper thiovanadate for magnesium-sodium hybrid battery according to claim 1, characterized in that: The process conditions for centrifugation in step 2) are: taking the cooled reaction solution and placing it in a centrifuge tube, centrifuging it alternately with deionized water and ethanol for 2-5 times, the centrifugation rate is 8000-12000rpm, each centrifugation time is 2-10min, and the supernatant is removed; the process conditions for drying are: drying in a vacuum oven at 50-70°C for 10-15h.